Correlação clínico-laboratorial e de imagem do lúpus eritematoso sistêmico e da esclerose múltipla no HC/FM/UFG em Goiânia/Goiás de 2009 a 2010: ênfase nas manifestações neurológicas - DINIZ, Denise Sisterolli (2011)
Systemic Lupus Erythematosus - LES is an autoimmune disease involving multiple systems. In the Central nervous system-SNC is one of his more severe manifestations. One of the frames of Lupus neuropsychiatric - LES-NP, is a Demyelinating Syndrome - SD. SD in rare cases, may be the first manifestation of LES, resembling multiple sclerosis - MS in their symptoms. MS is autoimmune disease with involvement of SNC with components, degenerative and inflammatory, which can produce autoantibodies and general symptoms that make your final diagnosis. The disease occurs more in young women than in men, typically evolve with outbreaks and remissions. In order to contribute to the diagnosis of these two illnesses, we proposed a comparative analysis, considering clinical, laboratory, and image aspects. As there is a lack of definition of SD, aims to contribute to the definition and establishment of standards of compromise of the SNC by SD of LES-NP, comparing patients with LES-NP and MS (the prototype of CNS demyelinating disease), attended in rheumatology and neurology of the HC/FM/UFG, Goiania. GO, from 2009 to 2010, according to the demographic aspects (sex and age), clinical (time of illness, functional systems and EDSS), laboratory (Autoantibodies and liquid Cerebroespinhal - LCR), image (Conventional magnetic resonance - RM) and Neuropsychological - NPS (cognitive and emotional). It is one epidemiological, analytical and comparative cross-sectional study of LES-NP and MS, which was approved by the CEP/HC/UFG. Were used in the survey questionnaires: an analysis of demographic and personal and family background; other symptoms; Neurological exams and NPS; Analysis: image by RM, laboratory of autoantibodies and LCR; and symptoms of depression and anxiety by Beck inventory (BAI and BDI). The results demonstrated an increased frequency in patients of age; time of disease; Visual symptoms; changes of sensitivity; of coordination; of the March; retention and urinary incontinence; changes of speech and swallowing; depressive and psychotic symptoms in family and personal history; WMHs in parietal and frontal lobes, occipitais, corpus callosum, periventricular, justacortical, brain stem; the cerebellum; spinal cord and the Barkhof and Tintoré criteria - CBT. Other findings in the RM were: infarcts; Vasculitis; menigioma and thrombosis in patients with LES-NP. The involvement of SNC in LES was measured by clinical symptomatology, neurological examination, EDSS, image findings and neuropsychological tests. RM was predictive analytics to relate workload post-lesional adaptation in brain regions typically involved in in. The application of CBT in patients with SD of LES-NP, associated with the qualitative assessment of WMHs may define the differences of neurological involvement pattern of injury of the SD of LES-NP, those at. The dosage of autoantibodies was predictive analytics for the diagnosis of LES, especially the anti DNA, the anti-ENA and the LAC, which were unique in the LES-NP. The clinical examination and laboratory research, neurological autoantibodies antinuclear antibodies and image by RM offers great security in diagnosis of the two diseases.Show that there are aspects of the involvement of the SD in LES needing new assessments, using the markers of neuronal injury, the more specific and with studies of Immunogenetics compared with in, the prototype of CNS demyelinating disease.